Autobiographical memory specificity and affect regulation: an experimental approach. - Raes, F; Hermans, D; de Decker, A; Eelen, P; Williams, J (2003)
This study investigated J. M. G. Williams's (1996) affect-regulation hypothesis that level of specificity of autobiographical memory (AM) is used to minimize negative affect. It was found that a negative event leads to more reports of subjective stress in high- as compared with low-specific participants. Also, afterward, high-specific participants rated their unprompted memories for the event as more unpleasant. The results indicate that, relative to high specificity, being less specific in the retrieval of AMs is associated with less affective impact of a negative event. Results are discussed within the affect-regulation model. It is suggested that future research take a more functional perspective on AM specificity.